A wear-resistant metal composite material and preparation method thereof
By introducing specific refined fluxes on the surface of low alloy liquid steel, a low melting point slag shell is formed, which blocks air contact and promotes contact between high-chromium alloy cast iron and low alloy liquid steel, the problems of interface pores and slag inclusions are solved, and the interface combination is improved Strength and wear resistance extend service life.
Patent Information
- Application Number
- CN202211686406.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The existing metal composite materials form pores and non-metallic slag inclusions at the interface, resulting in a decrease in wear resistance and crack resistance, low interface strength, and easy peeling of the composite layer.
The surface of low alloy steel is introduced to refining fluxes, including Na2O, ZrO2, SiO2 and B2O3, to form a low melting point slag shell, blocking the contact between the air and the steel surface, and promoting the contact between the high-chromium alloy cast iron melt and the low-alloy steel surface, realizing the Metallurgy combines to eliminate interfacial pores and slag inclusions and improve interfacial bonding strength.
Effectively eliminate interface pores and non-metallic slag inclusions, improve interface bonding strength, enhance wear resistance, extend service life, and reduce the degree of composite layer shedding.
Smart Images

Figure CN115958184B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal wear-resistant composite materials, and in particular relates to a metal wear-resistant composite material and a preparation method thereof. Background Art
[0002] Metal wear-resistant materials are the main materials for wear-resistant parts of crushers such as ball mills and hammer crushers. In order to improve the wear resistance of wear-resistant parts, bimetallic composite materials are used. High-wear-resistant high-chromium alloy cast iron is used in the service area of the component, and high-strength and toughness low-alloy steel is used in the installation area. The composite method is to first cast low-alloy steel from the bottom and then cast high-chromium alloy cast iron from the top.
[0003] However, the existing composite method has the following significant disadvantages: 1. A high melting point oxide film is generated on the surface of the poured low alloy steel liquid, and then high chromium alloy cast iron is poured, which easily forms pores and non-metallic slag inclusions at the interface; 2. In order to promote the floating of the high melting point oxide film, the casting temperature of the high chromium alloy cast iron melt is usually increased, but the casting temperature of the high chromium alloy cast iron melt is high, and this part shrinks greatly, resulting in loose shrinkage, pores, cracks and other casting defects on the cross section of the entire working layer. The above-mentioned disadvantages all lead to uneven macro and micro structures, reduced wear resistance and crack resistance, and low interface strength, easy peeling of the composite layer and reduced wear resistance due to abrasive wear.
[0004] UA113945U and UA10827U disclose that after casting alloy steel, an oxygen-impermeable coating is applied on its surface at a temperature lower than the solidus temperature of steel by 250±20°C, and high chromium cast iron melt is cast from the riser to the alloy steel slag layer (coating). The steel slag layer floats up into the riser due to its lighter specific gravity than the high chromium cast iron melt, and the alloy steel and high chromium cast iron are connected to achieve bimetallic composite. However, these two patents have the following problems: 1) The oxygen-impermeable coating applied on the surface at a temperature lower than the solidus temperature of alloy steel by 250±20°C can dilute the slag. Under the heat of the high chromium cast iron melt and the impact of pouring from the riser to the alloy steel slag surface, the slag floats up into the riser, but due to the low temperature of the alloy steel, the high chromium cast iron melt is difficult to connect the alloy steel well, and the interface bonding is poor; 2) The riser neck is the same size as the product use surface, and it is difficult to remove the riser in the later stage. In order to obtain the shape and size specified by the use surface, the processing cost is high.
[0005] Therefore, there is an urgent need in the art for a metal composite method that can overcome the above-mentioned shortcomings and enhance the interface bonding strength. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the prior art that the metal composite method will form pores and non-metallic slag inclusions at the interface, resulting in a decrease in wear resistance and crack resistance, and to provide a metal wear-resistant composite material and a preparation method thereof. The preparation method can eliminate defects such as interface pores and non-metallic slag inclusions, improve interface bonding strength, and improve wear resistance.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a metal wear-resistant composite material, comprising the following steps: casting low alloy steel into a casting mold, introducing a refining flux on its surface, and then casting a high chromium alloy cast iron; wherein the chemical composition of the refining flux includes, by mass percentage: 25-30wt% Na 2 O, 5-8wt% ZrO 2 , 7-9wt%SiO 2 , 1-2wt%NiO, 51-62wt%B 2 O 3 .
[0008] In some preferred embodiments, the refining flux is introduced within 20-50 seconds after the low alloy steel is cast.
[0009] More preferably, the refining flux is introduced within 40-50 seconds after the low alloy steel is cast.
[0010] In some preferred embodiments, the amount of the refining flux added is 0.03-0.06 g / cm relative to the surface area of the low alloy steel liquid after casting. 2 .
[0011] In some preferred embodiments, the refining flux is in powder form with a particle size of 0.5-1 mm.
[0012] In some preferred embodiments, the casting temperature of the high chromium alloy cast iron is 1350-1375°C.
[0013] More preferably, the casting temperature of the high chromium alloy cast iron is 1355-1370°C.
[0014] In some preferred embodiments, the casting temperature of the low alloy steel is 1560-1580° C., and the casting speed is 0.8-1.2 kg / s.
[0015] In some preferred embodiments, the structure of the casting mold includes:
[0016] A mold cavity is arranged in the middle of the mold;
[0017] A pouring cavity is arranged at one side of the mold cavity, and its bottom is L-shaped and is first connected with the middle and upper part of the mold cavity, and its top is open, and is used for pouring low alloy steel and high chromium alloy cast iron into the mold cavity;
[0018] A riser is arranged on the other side of the mold cavity, with an open top and a bottom side surface thereof being connected to the middle and upper part of the mold cavity for a second time, and the lowest horizontal line of the second connection is equal to the lowest horizontal line of the first connection, and the cross-sectional size of the riser neck of the riser is larger than the cross-sectional size of the casting cavity, so as to concentrate slag inclusions from the mold cavity into the riser while the riser is performing shrinkage compensation.
[0019] In some preferred embodiments, in terms of mass percentage, the carbon content of the low alloy steel is 0.25-0.5wt%, and the total content of alloying elements is less than 5wt%; the carbon content of the high chromium alloy cast iron is 2-3.5wt%, and the chromium content is 15-30wt%.
[0020] The second aspect of the present invention provides a metal wear-resistant composite material obtained by the preparation method of the first aspect, wherein the interface between the low alloy steel and the high chromium alloy cast iron in the metal wear-resistant composite material is a metallurgical bond.
[0021] The inventors of the present invention have found that when casting a low alloy steel melt to a specific position of a casting mold, Al in the low alloy steel melt 2 O 3 、SiO 2 , MnO and other slag float to the surface of the molten steel, and oxidize to form iron oxide Fe in contact with the surface of the molten steel and air. 2 O 3 , together forming a slag layer, due to the heat dissipation of the slag layer to form a hard slag shell, the heat of the casting high-chromium alloy cast iron melt melts the hard slag shell, and floats to the riser, so that the high-chromium alloy cast iron liquid and the low-alloy steel liquid are in direct contact to form a metallurgical interface, and the stable preparation of the bimetallic composite material is achieved. However, the existing method is difficult to break the hard slag shell and float it, slag inclusions or pores appear on the interface, the interface strength is low, and the composite layer is easy to peel off during operation. For this reason, the casting temperature of the high-chromium alloy cast iron melt is usually increased to melt the slag shell, but the high-chromium alloy cast iron liquid and the low-alloy steel liquid are often mixed. Moreover, due to the high casting temperature, the high-chromium alloy cast iron part is prone to cracks or looseness, affecting the composite effect.
[0022] The present invention introduces a refining flux of specific composition into the low alloy steel liquid surface. The various components of the present invention are used synergistically to form a low melting point slag from the hard slag shell and to block the air and the low alloy steel liquid surface. The present invention can not only prevent metal oxidation in a short time, but also allow the low melting point oxide to rush into the riser on the other side of the mold cavity under the impact force of the subsequent casting of high chromium alloy cast iron melt through one side of the mold cavity, which is beneficial to the surface contact between the low alloy steel liquid surface and the high chromium alloy cast iron melt, realize the mutual diffusion of low alloy steel and high chromium alloy cast iron at the interface to form a metallurgical bond, eliminate interface pores and non-metallic slag inclusions, purify the interface, and is beneficial to eliminate the looseness, porosity, cracks and other casting defects in the service area, thereby improving the interface bonding strength and wear resistance.
[0023] In the preferred casting structure of the present invention, the slag inclusions can be concentrated in the riser next to it, and the riser of the present invention has a shrinkage compensation function. Combined with the specific method of the present invention, it is more conducive to the rapid metallurgical bonding of the interface of the low-alloy steel and high-chromium alloy cast iron bimetallic composite, and is more conducive to concentrating all the slag inclusions in the riser. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 It is a schematic diagram of the structure of casting low alloy steel according to the present invention.
[0026] Figure 2 It is a schematic diagram of the structure of the spraying refining flux of the present invention.
[0027] Figure 3 It is a schematic diagram of the structure of casting high chromium alloy cast iron according to the present invention.
[0028] Figure 4 It is a schematic diagram of the structure of the composite material casting obtained after solidification of the present invention.
[0029] Figure 5 This is a scanning electron microscope image of the interface of the composite material of Example 1 of the present invention.
[0030] Figure 6 This is a scanning electron microscope image of the interface of the composite material obtained in Example 1 without adding a refined flux.
[0031] Figure 7 This is a scanning electron microscope image of the interface of the composite material obtained in Example 1 without adding a refined flux.
[0032] Figure 8This is a scanning electron microscope image of the interface of the composite material obtained in Comparative Example 2.
[0033] Fig. 9 This is a scanning electron microscope image of the interface of the high chromium alloy cast iron portion of the composite material obtained in Comparative Example 3.
[0034] Fig.10 This is a photograph of the composite material obtained in Example 4, showing a cross section of the composite vertical interface.
[0035] Description of Reference Numerals
[0036] 1. Low alloy steel, 2. Casting mold, 3. Refining flux, 4. High chromium alloy cast iron, 5. Interface, 6. Slag inclusions, 7. Riser; 201. Casting cavity, 202. Mold cavity, 203. Riser. DETAILED DESCRIPTION
[0037] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0038] The first aspect of the present invention provides a method for preparing a metal wear-resistant composite material, comprising the following steps: casting low alloy steel into a casting mold, introducing a refining flux on the surface of the casting mold, and then casting a high chromium alloy cast iron; wherein the chemical composition of the refining flux includes, by mass percentage, 25-30wt% Na 2 O, 5-8wt% ZrO 2 , 7-9wt%SiO 2 , 1-2wt%NiO, 51-62wt%B 2 O 3 .
[0039] In the refining flux of the present invention, B 2 O 3 Low melting point, combined with an appropriate amount of Na 2 O can form a low-melting-point glass phase with the oxides in the hard slag shell, which is beneficial to the casting of high-chromium alloy cast iron melt to break the slag and achieve surface contact with the low-alloy steel melt. The appropriate amount of NiO absorbs oxygen in the air to block the contact between the air and the low-alloy steel liquid surface and forms a thin oxygen-content atmosphere layer on the liquid surface to prevent further oxidation of the low-alloy steel surface. The appropriate amount of ZrO 2There are three crystal forms: monoclinic phase, tetragonal phase and cubic phase. The monoclinic phase is maintained at room temperature, and it transforms into tetragonal phase from room temperature to the temperature of low alloy steel liquid surface. The volume shrinks, and the glass phase forms microscopic pores, which is conducive to further contact between the high chromium alloy cast iron melt and the low alloy steel liquid surface. At the same time, with the appropriate amount of SiO 2 The viscosity of the glass slag can be adjusted by the combination; the synergy of the components can break the hard slag shell at a relatively low temperature, and the high chromium cast iron melt is poured from one side of the mold cavity, flushing the slag into the riser on the other side of the mold cavity, promoting the surface contact of the bimetallic and forming a low-oxygen atmosphere layer on the surface of the steel liquid to further prevent oxidation; thereby enhancing the interface bonding strength. 2 If the content is too high, the glass phase slag has high viscosity, and the slag is difficult to flush into the riser, and it will enter the high chromium alloy cast iron and easily produce slag inclusions; if Na 2 If the O content is too high, the viscosity of the glassy slag will be low, which may easily lead to the mixing of high-chromium alloy cast iron melt with low-alloy steel.
[0040] Preferably, the chemical composition of the refining flux includes, by mass percentage: 27.5-30% Na 2 O, 6.5-8% ZrO 2 , 8-9% SiO 2 , 1-2% NiO, 51-57% B 2 O 3 This preferred solution is more conducive to improving the service life and interface bonding strength, and further reducing the degree of shedding of the composite layer.
[0041] In some preferred embodiments, the refining flux is introduced within 20-50 seconds after the low alloy steel is cast. More preferably, the refining flux is introduced within 40-50 seconds after the low alloy steel is cast.
[0042] The introduction timing of the refining flux of the present invention is controlled within the above preferred range, which can timely promote the hard slag shell to form low-melting-point slag and quickly block the contact between air and the low-alloy steel liquid surface, and is more conducive to improving the interface bonding strength.
[0043] The introduction of the present invention can be carried out by spraying or the like.
[0044] In some preferred embodiments, the amount of the refining flux added is 0.03-0.06 g / cm relative to the surface area of the low alloy steel liquid after casting. 2 Under this preferred solution, the low melting point slag with suitable viscosity can be evenly spread to the surface of the low alloy steel liquid, and it is convenient for the low melting point slag to enter the riser in the subsequent casting process of high chromium alloy cast iron.
[0045] In some preferred embodiments, the refining flux is in powder form with a particle size of 0.5-1 mm. In this preferred embodiment, the refining flux is in powder form for easy spraying, and its appropriate particle size is more conducive to rapid heating and promoting the rapid formation of low-melting-point slag from the hard slag shell.
[0046] Those skilled in the art can select the preparation method of the refining flux according to the needs, as long as it has the above composition. Preferably, the refining flux is obtained by the following method: 2 O and SiO 2 Mix water glass with ZrO 2 、NiO、B 2 O 3 Grind and mix evenly, then dry and crush.
[0047] In some preferred embodiments of the present invention, the casting temperature of the high chromium alloy cast iron is 1350-1375°C. Under this preferred scheme, only a lower casting temperature is used, and the casting temperature of the high chromium alloy cast iron is lower than the conventional casting temperature (generally 1500-1540°C in the prior art), which can not only ensure smooth casting, but also facilitate grain refinement, good shrinkage compensation effect, and is more conducive to eliminating looseness, pores, cracks and other casting defects in the service area, and the wear resistance of the obtained component is further improved; and it is coordinated with the refining flux to achieve high-quality and stable preparation of metal wear-resistant composite materials.
[0048] More preferably, the casting temperature of the high chromium alloy cast iron is 1355-1370°C.
[0049] In some preferred embodiments, the casting temperature of the low alloy steel is 1560-1580° C., and the casting speed is 0.8-1.2 kg / s.
[0050] In some preferred embodiments, Figure 1 As shown, the structure of the casting mold 2 includes:
[0051] The mold cavity 202 is arranged in the middle of the mold 2;
[0052] A pouring cavity 201 is arranged at one side of the mold cavity 202, and its bottom is L-shaped and is first connected with the middle and upper part of the mold cavity 202, and its top is open, and is used for pouring low alloy steel 1 and high chromium alloy cast iron into the mold cavity 202;
[0053] A riser 203 is arranged on the other side of the mold cavity 202, with an open top and a bottom side surface thereof being connected to the middle and upper part of the mold cavity 202 for a second time, and the lowest horizontal line of the second connection is equal to the lowest horizontal line of the first connection, and the cross-sectional dimension of the riser neck of the riser 203 is larger than the cross-sectional dimension of the casting cavity 201, so as to concentrate slag inclusions from the mold cavity 202 into the riser 203 while the riser 203 is performing shrinkage compensation.
[0054] More preferably, the minimum radial dimension of the cross section of the riser neck of the riser 203 is 2-3 times the minimum radial dimension of the cross section of the casting cavity 201 .
[0055] In some preferred embodiments, the carbon content of the low alloy steel is 0.25-0.5wt%, and the total content of alloy elements is less than 5wt%, measured in mass percentage.
[0056] In some preferred embodiments, the high chromium alloy cast iron has a carbon content of 2-3.5 wt % and a chromium content of 15-30 wt %, measured in mass percentage.
[0057] Those skilled in the art may also adopt other conventional process steps to prepare metal wear-resistant composite materials. For example, preferably, the preparation method further comprises: when the temperature of the composite casting obtained after casting the high-chromium alloy cast iron is lower than 200°C, removing the riser and the casting system (such as a casting mold) to obtain the casting, and then performing optional heat treatment to obtain the metal wear-resistant composite material product. The metal wear-resistant composite material product may include a hammer head, a plate hammer, a liner, a bucket tooth, a tooth plate, etc.
[0058] The second aspect of the present invention provides a metal wear-resistant composite material obtained by the preparation method of the first aspect, wherein the interface between the low alloy steel and the high chromium alloy cast iron in the metal wear-resistant composite material is a metallurgical bond.
[0059] The metal wear-resistant composite material provided by the invention has good interface bonding, no inclusions on the interface, high interface bonding strength, long service life, and extremely little shedding of the composite layer and no cracks.
[0060] The present invention is further elaborated in detail below in conjunction with specific embodiments. Among them, the interface strength is measured by the tensile strength test method. The service life is measured by a three-body abrasive wear test. Specifically, the three-body abrasive wear test is carried out on a three-body wear testing machine, which is mainly composed of a motor, a spindle, a loading weight, a loading guide mechanism, a sample clamping mechanism, a rail, a sand collection mechanism, a dust prevention mechanism and a control system. It is an existing device; wherein the outer diameter of the rail material is 400mm and the width is 20mm. The spindle speed is 1r / min-90r / min steplessly adjustable, and the load is loaded by weights. The maximum load of a single axis is 5kg. Abrasives can be selected according to different wear and tear industries and mines. The present invention uses quartz sand with a hardness of HV1000-1200 and a particle size of 60-120 mesh; generally speaking, the wear resistance of a material can be expressed in the form of mass loss, volume loss, wear rate and relative wear resistance; the present invention is expressed in terms of relative wear resistance.
[0061] Example 1
[0062] A method for preparing a composite hammer head is as follows:
[0063] like Figure 1 As shown, low alloy steel 1 melt (by mass, carbon content is 0.35%, total alloying element content is 4.5%) is quantitatively cast through the casting cavity 201 of the casting mold 2, the casting temperature is 1560°C, and the casting speed is set to 0.9 kg / s. 35 seconds after casting the low alloy steel, as shown in FIG. Figure 2 As shown, refining flux 3 is sprayed on the surface through the riser neck of riser 203, and the added amount is 0.04 grams per square centimeter of the surface area of the low alloy steel liquid. The refining flux is powdery and its particle size is 0.5-1mm; wherein the refining flux 3 is composed of: 27wt% Na 2 O, 6wt% ZrO 2 , 7.5wt%SiO 2 , 1.5wt% NiO, the rest is B 2 O 3 .like Figure 3 As shown, the wear-resistant high chromium alloy cast iron 4 melt (chromium content of 15% and carbon content of 3.5% by mass) is poured into the same pouring cavity 201 of the low alloy steel 1 at a casting temperature of 1360°C; Figure 4 As shown, after the temperature of the composite casting obtained after solidification is lower than 200°C, the riser 7 is removed, and the slag inclusions 6 gather in the riser 203 and float to the upper part. The heat treatment quenching temperature is 950°C, and the wear-resistant composite material hammer product is obtained. The interface electron microscope image of the product is shown in Figure 5 As shown, it can be seen that the interface between the low alloy steel 1 and the high chromium alloy cast iron 4 diffuses mutually and the interface bonding is good.
[0064] The test results show that the bonding strength of the composite hammer interface 5 of this embodiment reaches 580 MPa, and the composite layer falls off by 0.2%; the service life is increased by 50% compared with the comparative example 1 without adding refining flux under the same conditions.
[0065] Example 2
[0066] The method of Example 1 is followed, except that the refining flux composition is: 28wt% Na 2 O, 6wt% ZrO 2 , 7.5wt%SiO 2 , 1.5wt% NiO, the rest is B 2 O 3 .
[0067] The same test was carried out, and the results showed that the composite hammer interface bonding strength of this embodiment reached 590MPa, and the composite layer fell off by 0.09%; the service life was increased by 50% compared with the comparative example 1 without adding refining flux under the same conditions.
[0068] Example 3
[0069] The method of Example 1 is followed, except that the refining flux composition is: 27wt% Na 2 O, 7wt% ZrO 2 , 8wt%SiO 2 , 1.5wt% NiO, the rest is B 2 O 3 .
[0070] The same test results show that the composite hammer interface bonding strength of this embodiment reaches 595MPa, and the composite layer falls off by 0.085%; the service life is increased by 50% compared with the comparative example 1 without adding refining flux under the same conditions.
[0071] Example 4
[0072] The method of Example 1 is carried out, except that the refining flux is composed of:
[0073] 28wt%Na 2 O, 7wt% ZrO 2 , 8wt%SiO 2 , 1.5wt% NiO, the rest is B 2 O 3 .
[0074] The same test results show that the composite hammer interface bonding strength of this embodiment reaches 600MPa, and the composite layer falls off by 0.08%; the service life is increased by 55% compared with the comparative example 1 without adding refining flux under the same conditions.
[0075] Example 5
[0076] The method of Example 4 is referred to, except that 45 seconds after casting the low alloy steel, a refining flux is sprayed on the surface thereof.
[0077] The same test results show that the composite hammer interface bonding strength of this embodiment reaches 620MPa, and the composite layer falls off by 0.05%. The service life is increased by 57% compared with the comparative example 1 without adding refining flux under the same conditions.
[0078] Example 6
[0079] The method of Example 4 is used, except that the casting temperature of the wear-resistant high chromium alloy cast iron melt is 1375°C.
[0080] The same test results show that the composite hammer interface bonding strength of this embodiment reaches 590MPa, and the composite layer falls off by 0.10%. The service life is increased by 53% compared with the comparative example 1 without adding refining flux under the same conditions.
[0081] Example 7
[0082] The method of Example 6 is referred to, except that 45 seconds after casting the low alloy steel, a refining flux is sprayed on its surface.
[0083] The same test was carried out, and the results showed that the interface bonding strength of the composite hammer head of this embodiment reached 650 MPa, and the composite layer did not fall off; the service life was increased by 60% compared with the comparative example 1 without adding refining flux under the same conditions.
[0084] Comparative Example 1
[0085] The method of Example 1 is followed, except that no refining flux is added.
[0086] The interface electron microscopy image of the composite material obtained is shown in Figure 6 and Figure 7 As shown, it can be seen that slag inclusions appear at its interface, and the composition of the slag inclusions is C 8.58wt%, O 38.77wt%, Si 0.78wt%, Cr 1.67wt%, Mn 1.16wt%, Fe49.04wt%; and the high chromium cast iron part has cracks.
[0087] The same test was carried out, and the results showed that the interface bonding strength of the composite material hammer head of this embodiment reached 430 MPa, and the composite layer fell off by 10%.
[0088] Comparative Example 2
[0089] The method of Example 7 is followed, except that the refining flux composition is: 32wt% Na 2 O, 7wt% ZrO 2 , 8wt%SiO 2 , 1.5wt% NiO, the rest is B 2 O 3 .
[0090] The interface of the composite material is as follows Figure 8 As shown, it can be seen that the high chromium alloy cast iron (referred to as high chromium cast iron in the figure) melt is mixed into the low alloy steel (referred to as alloy steel in the figure).
[0091] The same test was carried out, and the results showed that the composite hammer interface bonding strength of this embodiment reached 500MPa, and the composite layer fell off by 2%; the service life was increased by 40% compared with the comparative example 1 without adding refining flux under the same conditions.
[0092] Comparative Example 3
[0093] The method of Example 7 is followed, except that the refining flux composition is: 28wt% Na 2 O, 9wt% ZrO 2 , 10wt%SiO 2 , 1.5wt% NiO, the rest is B 2 O 3 .
[0094] The interface of the composite material is as follows Fig. 9 As shown, it can be seen that the high chromium alloy cast iron part has slag inclusions, and the slag inclusion composition is C11.19wt%, N 8.43wt%, O 28.21wt%, Na 0.75wt%, Al 0.13wt%, Si5.34wt%, S 0.29wt%, Zr 5.49wt%, K 0.26wt%, Cr 10.50wt%, Mn 0.29wt%, and Fe34.13wt%.
[0095] The same test was carried out, and the results showed that the composite hammer head interface bonding strength of this embodiment reached 480MPa, and the composite layer fell off by 3%; the service life was increased by 30% compared with the comparative example 1 without adding refining flux under the same conditions.
[0096] Comparative Example 4
[0097] The method of Example 7 is followed, except that the refining flux composition adopts the formula of the coating layer of UA10827U: 22wt% Na 2 O; 2.5wt% ZrO 2 ; 2wt%K 2 O, 2wt%F2 (Total fluoride); 4wt%SiO 2 ; 0.4wt% NiO; the rest is B 2 O 3 .
[0098] And in this comparative example, UA10827U is used Figure 1-Figure 4 In the model shown, low alloy steel is poured on one side of the bottom of the mold cavity at a casting temperature of 1600°C. After 2.5 minutes, the surface of the low alloy steel is pierced with steel bars, which cannot penetrate into the low alloy steel melt. Flux is sprayed through the riser on the upper part of the mold cavity. Wear-resistant high chromium cast iron melt is then poured through the riser on the upper part at a casting temperature of 1400°C. After solidification and cooling, the riser is removed, heat treatment is performed, and the mold is processed to the size and shape required by the drawing.
[0099] The interface of the composite material is as follows Fig.10 As shown, it can be seen that the interface composite between high chromium alloy cast iron and low alloy steel is not good.
[0100] The same test was carried out, and the results showed that the composite hammer interface bonding strength of this embodiment reached 300 MPa, and the composite layer fell off by 30%; the service life was increased by 30% compared with the comparative example 1 without adding refining flux under the same conditions.
[0101] It can be seen from the above embodiments and comparative examples that the composite material obtained by the embodiments of the present invention has good interface bonding, no inclusions on the interface, high interface bonding strength, long service life, and significantly less composite layer shedding and no cracks.
[0102] Further, it can be seen from Examples 4 and 5, 6 and 7 that the preferred timing of introducing the refining flux of the present invention is more conducive to improving the service life and interface bonding strength, and further reducing the degree of shedding of the composite layer. It can be seen from Examples 4 and 6 that the preferred high chromium alloy cast iron melt of the present invention is more conducive to improving the service life and interface bonding strength, and further reducing the degree of shedding of the composite layer.
[0103] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a metal wear-resistant composite material, characterized in that: The following steps are involved: Casting low alloy steel into a casting mold, introducing a refining flux on the surface of the casting mold, and then casting high chromium alloy cast iron; wherein the chemical composition of the refining flux includes, by mass percentage, 25-30wt% Na2O, 5-8 wt% ZrO2, 7-9 wt% SiO2, 1-2 wt% NiO, 51-62 wt% B2O3, the casting temperature of the high chromium alloy cast iron is 1350-1375°C; the casting temperature of the low alloy steel is 1560-1580°C, and the pouring speed is 0.8-1.2kg / s; The structure of the casting mold comprises: A mold cavity, which is arranged in the middle of the mold; A pouring cavity is arranged at one side of the mold cavity, and its bottom is L-shaped and is first connected with the middle and upper part of the mold cavity, and its top is open, and is used for pouring low alloy steel and high chromium alloy cast iron into the mold cavity; A riser is arranged on the other side of the mold cavity, with an open top and a bottom side surface thereof being connected to the middle and upper part of the mold cavity for a second time, and the lowest horizontal line of the second connection is equal to the lowest horizontal line of the first connection, and the cross-sectional size of the riser neck of the riser is larger than the cross-sectional size of the casting cavity, so as to concentrate slag inclusions from the mold cavity into the riser while the riser is performing shrinkage compensation.
2. The preparation method according to claim 1, characterized in that: The refining flux is introduced within 20-50 seconds after the low alloy steel is cast.
3. The preparation method according to claim 2, characterized in that: The refining flux is introduced within 40-50 seconds after the low alloy steel is cast.
4. The preparation method according to claim 1, characterized in that: Relative to the surface area of the low alloy steel liquid after casting, the amount of the refining flux added is 0.03-0.06 g / cm 2 .
5. The preparation method according to claim 1, characterized in that: The refining flux is in powder form with a particle size of 0.5-1 mm.
6. The preparation method according to claim 1, characterized in that: In terms of mass percentage, the carbon content of the low alloy steel is 0.25-0.5 wt%, and the total content of alloy elements is less than 5 wt%; the carbon content of the high chromium alloy cast iron is 2-3.5 wt%, and the chromium content is 15-30 wt%.
